PERENCANAAN LANSKAP KOTA PARIAMAN PROVINSI SUMATERA BARAT BERBASIS MITIGASI TSUNAMI - Fadhilatul Ihsan; Qodarian Pramukanto (Jurnal Lanskap Indonesia, 2017)
The city of Pariaman lied on vurnerable area of two continental plates of Eurasian and Indo-Australian plates and passed by Semangko fault line as well. Based on the index map Threats Tsunami in Indonesia by the National Disaster Management Agency (BMKG), the coastal west area of Sumatra Island is an area of the tsunami hazard. The purpose of this study is to arranging landscape plan of the city of Pariaman based on tsunami mitigation. The method used in this study consists of five phases starting from the preparation, inventory, analysis, and landscape planning. The spasial analysis was conducted to determine the level of tsunami hazard and hazard risk to tsunami in the city of Pariaman which are consist of sensitivity analysis, and analysis of vulnerablility to tsunami. The factors that used in sensitivity analysis are seismicity and run up of tsunami (12 m height), while the vulnerable analysis factors are elevation, slope, coastal morphology, land use, distance from the shoreline, and the distance from the river. The results of analysis show that most area of Pariaman City can be classified into low level hazard risk to tsunami. Based on hazard risk classifica-tion can be developed the concept to proceed landscape plan. Landscape plan can be arranged into protective space, limited use space and development space.